2014
DOI: 10.1590/s0102-05362014000200021
|View full text |Cite
|
Sign up to set email alerts
|

Densidade de plantio e genótipos de tomateiro cereja em sistema fechado de cultivo em substrato

Abstract: Plant density and cherry tomato genotypes in closed substrate growing systemThe cultivation of cherry tomato in closed substrate systems (which promote reuse of the drained solution) is fundamental in order to reduce water and fertilizer waste and environmental pollution. However, the literature background is scarce. This work aimed to establish the influence of different plant densities (2.9; 3.9; 4.7; 5.9 and 7.8 plants m -2 ) on growth, yield and fruit quality of two cherry tomato genotypes ('Cereja Vermelh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 21 publications
5
13
0
10
Order By: Relevance
“…AZEVEDO et al (2010) andPEIL et al (2014) verified an increased cherry tomato production in dense cultures, which corroborated the results found in this study. High density planting leads to a reduction in the number of tomatoes per plant due to increased competition between plants.…”
Section: ------------------------------------------------------------supporting
confidence: 90%
See 1 more Smart Citation
“…AZEVEDO et al (2010) andPEIL et al (2014) verified an increased cherry tomato production in dense cultures, which corroborated the results found in this study. High density planting leads to a reduction in the number of tomatoes per plant due to increased competition between plants.…”
Section: ------------------------------------------------------------supporting
confidence: 90%
“…Table 1 -Number of observations (n), minimum, maximum, mean, variance, standard deviation (SD), and coefficient of variation (CV%) of the variables mean fruit length per plant (MFL, in cm), mean fruit width per plant (MFWd, in cm), mean fruit weight per plant (MFW, in g), number of bunches per plant (NBP), number of fruits per bunch (NFB), number of fruits per plant (NFP), and total fruit weight per plant (TFW, in g) observed in two uniformity trails with cherry tomato. Thus, individually, cherry tomato fruits are weak drains (HEUVELINK, 1997;PEIL et al, 2014). The low magnitude linear relationship between the variable TFW and the variables MFL, MFWd, and MFW, and the high magnitude relationship between the variables NBP, NFP, and NFB indicated that, individually, the fruits have little influence on the plant's total production.…”
Section: Resultsmentioning
confidence: 99%
“…The Grape cultivar presented a 14 % higher TSS value (7.38) than that measured in the fruits of the Cherry cultivar (6.34). Both values can be considered adequate according to the results obtained by Peil et al (2014) for Cherry-type fruits and Takahashi and Cardoso (2015) for Grape-type fruits. The largest final stem length and the largest dry matter partition for this organ were observed for the Grape cultivar, which on the other hand presented lower dry matter partition to leaves (Table 2).…”
Section: Resultsmentioning
confidence: 97%
“…In the southern region of Brazil, an important rice producer, rice husk is abundant, as it is the residue of the grain processing industries. Raw rice husk has high aeration space and low chemical activity and can be successfully used as an isolated substrate in recirculating systems for mini tomatoes (Peil, Albuquerque Neto, & Rombaldi, 2014) as well as for other cultivated vegetable fruits such as melon (Duarte, Peil, Bacchis, & Strassburguer, 2008) and zucchini (Strassburger, Peil, Fonseca, Aumonde, & Mauch, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Raw rice husk, a low-cost, easily available material in Rio Grande do Sul, has been used alone as a cultivation substrate with a high degree of success for other fruit plants (Duarte et al, 2008;Strassburger et al, 2011), and even for small tomato varieties (Peil et al, 2014) in closed systems. However, the presence of organic compost at a small ratio in the mixture should increase the substrate buffer capacity and facilitate nutrient solution management, increasing water and mineral nutrients storage capacity and, therefore, enhancing crop yield.…”
Section: Introductionmentioning
confidence: 99%